Analisis Daya Saing Ekspor Karet Indonesia ke Negara Amerika Serikat dan Jepang - Ridho Christiadi Simbolon; Mutiara Az-zahra; Yolanda Desi Anggraini Silalahi; Reyhani Intan Sabrina; Rasidin Karo Karo Sitepu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Indonesia is in second place after Thailand which is one of the world's largest rubber producers. Indonesia is also the second largest rubber producing country in the world which plays an important role in meeting international market demand. The two countries that most often export rubber are the United States and Japan. Analyzing the competitiveness of Indonesian rubber exports to Japan and America is the aim of this research. Secondary data in the form of time series and cross-sectional data between individuals for the 2018–2022 period was obtained from the Trade map and BPS. This analytical method evaluates the competitive advantage of natural rubber in America and Japan using the Export Product Dynamics (EPD) and Revealed Comparative Advantage (RCA) methods to identify comparative advantages. The results of this analysis show that in 2019 and 2020, Indonesian rubber commodity exports to the US have a unique comparative advantage compared to Japan which does not have a comparative advantage. In terms of competitiveness, Indonesian rubber is relatively uncertain compared to America and Japan. Rubber producers in Indonesia and the government must be able to collaborate to improve the competitive position of Indonesian rubber exports in order to increase competitive and comparative advantages and maintain the stability of Indonesia's competitiveness against America and Japan.